The prince : the original classic - Machiavelli, Niccolò, 1469-1527. (England : Penguin Books, 2009)
Machiavelli's famously controversial work, is a leadership classic. This was the first book of its type to promise secrets of time management, presentations, change management and interview skills. With simple prose and straightforward logic Machiavelli's study of attaining power is relevant for any modern reader seeking to make their way in the world
"Based on the complete 1910 edition of The Prince, by Niccolo Machiavelli, translated by Ninian Hill Thomson, published by P.F. Collier and Son Company, New York"--T.p. verso.
Keywords: Political science -- Philosophy -- Early works to 1800.; Political ethics -- Early works to 1800.; State, The -- Early works to 1800.